Right ventricular outfl ow tract revalvulation using the Melody Valve: The next frontier - Buys, D.G.; Brown, S.C. (SA Heart Journal, 2017)
Congenital heart lesions with abnormal right ventricular outfl ow tract anatomy will require early surgical intervention. Re-intervention rates in these patients are high due to homograft degeneration. Until recently, surgery was the only treatment option for right ventricular outfl ow tract dysfunction. Percutaneous pulmonary valve implantation has been introduced as a new therapeutic alternative to prolong conduit life span and to reduce surgical re-intervention rates. Short- and mid-term results have been favourable and showed that it is a safe and effective therapy. These are reviewed with emphasis on the Melody valve.